LITERASI DETEKSI DINI RISIKO SINDROMA METABOLIK PADA IBU MAJELIS TAKLIM - Umar, Fitriani; Wahyuni Sari, Rasidah; Utami, Nabila; Megawati, Megawati (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The prevalence of degenerative diseases such as coronary heart disease, stroke and diabetes mellitus is increasing every year. A collection of metabolic disorders known as the metabolic syndrome such as obesity, hypertension, dyslipidemia and insulin resistance are at risk of causing cardiovascular disease and diabetes mellitus. Riskesdas data shows the high incidence of obesity and diabetes mellitus in women. The risk of this disease can be prevented if the public knows early and detects metabolic disorders that arise before the onset of the disease. This service activity aims to educate the community, especially the group of women from the taklim assembly about the risk of metabolic syndrome and early detection of metabolic syndrome parameters. Literacy activities are carried out in the form of counseling and leaflet distribution. Early detection of metabolic syndrome parameters includes measurement of abdominal circumference, examination of blood pressure and blood sugar levels. The participants of the activity were 22 women from the Ash-Salihin taklim assembly in Watang Soreang village, Parepare City. After giving the material, there was an increase in the knowledge of the mothers about the metabolic syndrome. 72.7% of the taklim mothers have metabolic syndrome parameters of abdominal circumference at risk and 27.3% have blood pressure at risk. It is hoped that after the service activities, mothers can prevent the risk of metabolic syndrome by implementing balanced nutrition and increasing physical activity.Â